2005
DOI: 10.1002/car.902
|View full text |Cite
|
Sign up to set email alerts
|

Representing children's views and best interests in court: an international comparison

Abstract: This paper provides a comparison of a number of alternative models of international practice in relation to the appointment and organization of guardians ad litem and other children's representatives in child care and family proceedings. The paper notes that, in their attempts to address the need for children to have representation in matters affecting their welfare, English-speaking countries have tended to conflate the two salient Articles of the United Nations Convention on the Rights of the Child, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…In the juge des enfants approach, parties (families) tend not to have legal representation (Freymond, 2001), even where the parents are mandated to attend against their will (as when they are suspected of child abuse). French judges also advise on child welfare matters relatively early in proceedings compared to other legal systems (Bilson & White, 2005). Furthermore, children are entitled to request a hearing (Bilson & White, 2005).…”
Section: Family Services: the European Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In the juge des enfants approach, parties (families) tend not to have legal representation (Freymond, 2001), even where the parents are mandated to attend against their will (as when they are suspected of child abuse). French judges also advise on child welfare matters relatively early in proceedings compared to other legal systems (Bilson & White, 2005). Furthermore, children are entitled to request a hearing (Bilson & White, 2005).…”
Section: Family Services: the European Modelmentioning
confidence: 99%
“…French judges also advise on child welfare matters relatively early in proceedings compared to other legal systems (Bilson & White, 2005). Furthermore, children are entitled to request a hearing (Bilson & White, 2005).…”
Section: Family Services: the European Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is evident in that, despite children's rights being a central focus in the current legislation and policies, judgments are often made during children's court proceedings as to whether or not children's wishes and views regarding their future are really in their own best interests or not (Bilson & White, 2005). Furthermore, Bilson and White (2005:236) found that in court settings, "the views of children are generally a secondary consideration to adult views of their best interests.…”
Section: Legislation Policies and Practicementioning
confidence: 99%